Systematic Theology. Volume 1: The Doctrine of God." By Katherine Sonderegger - Moore, A (Oxford University Press, 2017)
Many debates in contemporary theology can be interpreted as revolving around questions concerning the doctrine of God and, with it, the way in which we are to construe God’s relationship to the world, the way in which we are to understand ‘the world’, and the ways in which God may be spoken of faithfully. Anglican liberal theology of the last century – for example, the outstanding work of Maurice Wiles – tended to a relatively parsimonious doctrine of God, motivated as it was by the rather minimal affirmations a theologian could make in what was taken to be a philosophically justified way. It was not by accident that something like Deism was often the result. “Narrative” theologies – such as those of Barth, Moltmann, and Jenson – eschew the God of the philosophers and develop their doctrine of God from the Christ-event or, more narrowly, from the crucifixion of Jesus Christ. These approaches are robustly Trinitarian and seek to be guided by what the church receives as orthodoxy, but their “dramatic” structure can obscure the divine unity, and they can be regarded as sometimes blurring the distinction between God and the world. The question which arises is how to uphold the unity and aseity of God whilst allowing proportionate attention to the dramatis personae of salvation history. Katherine Sonderegger’s two volume systematic theology is of particular interest because in this, its first half, she aims to develop a doctrine of God that is focussed on and controlled by the divine unity (the second volume will address the doctrine of the Trinity), but she does so by taking her lead principally from Old Testament narratives rather than those of the New. Although Jesus Christ does not drop from view completely, the “drama” takes on a rather different character, and the doctrinal topics examined, like the conceptual problems discussed, remain substantially those that are generated for Christian readers of the the New Testament. So, as the author acknowledges, ‘this dogmatic volume cuts against the grain of modern Protestant dogmatics’: ‘it will be the aim of this dogmatics to honour Christ throughout a doctrine of God that is nevertheless not grounded nor derived from His incarnate life’ (p. xvii, sic, also p. xxiii, n. 5). The reason? ‘It is by setting forth the Divine Perfections, by allowing ourselves to glimpse how Scripture tells us Quid sit Deus that we recognize and bow down before the One God, incarnate’ (p. xviii). This book sets a very intriguing prospect before its readers.